The effects of long lasting physical exercise and training on kidneys functions - Żołądkiewicz, Katarzyna (Quality in Sport, 2019)
During long lasting physical exercise and physical training, a large number of changes occur in the human body. The body homeostasis is disturbed, and observed changes include kidney function. The most common observed symptom is a decrease in the amount of urine excreted due to an increase in the secondary absorption of water during exercise. During long lasting physical exercise the filtration in the glomeruli is impaired, and thus the composition of urine is changing. Differences in the amount of minerals excreted are noted, as a result of water loss, and urine osmolarity increases. Those changes are depend largely on the type of undertaken physical activity, its duration, as well as the individual predisposition of the examined physical active human. Therefore, in individual studies, the results differ significantly, and it is impossible to draw unequivocal conclusions.